2010
DOI: 10.1187/cbe.10-01-0006
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Information and Scientific Literacy: Promoting Literacy in Undergraduates

Abstract: The Association of College and Research Libraries recommends incorporating information literacy (IL) skills across university and college curricula, for the goal of developing information literate graduates. Congruent with this goal, the Departments of Biological Sciences and Information Science developed an integrated IL and scientific literacy (SL) exercise for use in a first-year biology course. Students were provided the opportunity to access, retrieve, analyze, and evaluate primary scientific literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…The small population of students who believed that online sources were very reliable have yielded interesting insights into students' misunderstanding of science (e.g., replication or finding information on more than one website) which has been documented among high school students [52]. This provides evidence of a link between information literacy and scientific literacy supporting many instructors' intuition about this connection and other work describing this connection [9,17]. Our findings suggest that students' overall knowledge of science and how science works is more closely related to their ability to judge the reliability of sources of science information than their choice of sources of information.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The small population of students who believed that online sources were very reliable have yielded interesting insights into students' misunderstanding of science (e.g., replication or finding information on more than one website) which has been documented among high school students [52]. This provides evidence of a link between information literacy and scientific literacy supporting many instructors' intuition about this connection and other work describing this connection [9,17]. Our findings suggest that students' overall knowledge of science and how science works is more closely related to their ability to judge the reliability of sources of science information than their choice of sources of information.…”
Section: Discussionmentioning
confidence: 60%
“…However, other work has also shown that (a) introductory astronomy courses are popular among a broad range of students [1,2,21], (b) the number of college science courses has been shown to be a strong predictor of civic scientific literacy, defined as having "(1) a basic vocabulary of scientific terms and constructs; and (2) a general understanding of the nature of scientific inquiry" (p. 273) in U.S. adults [14], and (c) a positive relationship exists between interest and attitudes and individuals' understanding in science [26][27][28]. In addition, there is ongoing interest in building students' scientific literacy comprised of multiple facets, including scientific knowledge and students' ability to locate and use information (information literacy) [9,16,17]. This study of introductory astronomy students investigates all these aspects together: the level of, and interactions between basic science knowledge, attitudes and beliefs, interests; sources of knowledge and ability to judge sources of information to give insights into these students with implications for the context of the introductory astronomy course.…”
Section: B Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations